2013
DOI: 10.1002/rrq.66
|View full text |Cite
|
Sign up to set email alerts
|

Young Children's Visual Attention to Environmental Print as Measured by Eye Tracker Analysis

Abstract: Environmental print, such as signs and product labels, consist of both print and contextual cues designed to attract the visual attention of the reader. However, contextual cues may draw young children's attention away from the print, thus questioning the value of environmental print in early reading development. Eye tracker technology was used to measure the extent that children attend to words in environmental print. The relationships between print fixations and letter and word knowledge, as well as differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 40 publications
4
17
1
Order By: Relevance
“…Extending this research on story books, a recent eye tracker study examined children's visual attention to words in environmental print (Neumann, Acosta, & Neumann, 2014). Pre-reading children (N = 39) aged 3 to 5 years were presented with photographs of nine different environmental print items (e.g., BUS STOP sign; HUNGRY JACK'S).…”
Section: Skilled Readers Have Progressed Throughmentioning
confidence: 99%
“…Extending this research on story books, a recent eye tracker study examined children's visual attention to words in environmental print (Neumann, Acosta, & Neumann, 2014). Pre-reading children (N = 39) aged 3 to 5 years were presented with photographs of nine different environmental print items (e.g., BUS STOP sign; HUNGRY JACK'S).…”
Section: Skilled Readers Have Progressed Throughmentioning
confidence: 99%
“…It has been suggested that books that contain a good deal of such print are an important vehicle for early literacy learning because they support the development of print awareness (Cetin & Bay, 2015; Zucker, Justice, & Piasta, 2009). This idea is based on the finding that preschool children pay more attention to writing that is large or bold or embedded in pictures than writing that does not have these characteristics (Neumann, Acosta, & Neumann, 2014; Neumann, Summerfield, & Neumann, 2015; Smolkin, Conlon, & Yaden, 1988; Smolkin, Yaden, Brown, & Hofius, 1992). When reading to children, moreover, teachers of preschool children appear to talk more often about the printed letters and words if books are high in print salience than if they are low (Dynia, Justice, Pentimonti, & Piasta, 2013; Zucker et al, 2009).…”
Section: Characteristics Of Print In Books For Preschool Childrenmentioning
confidence: 99%
“…The latter styles have been described as visually salient (Cetin & Bay, 2015), and studies suggest that they draw preschoolers’ attention (Neumann et al, 2014). We also coded whether the letters of the randomly chosen word were in a serif font (e.g., ‹k›) or a font without serifs (e.g., ‹›).…”
Section: Characteristics Of Print In Books For Preschool Childrenmentioning
confidence: 99%
See 2 more Smart Citations